Assessing the efficacy of regional anesthesia in reducing intraoperative blood loss during hysterectomy - Alamed, Mohammad Shakil; Moral, M. Salim; Alam, M. Hassnul; Siddique, Abul Bashar M.; Taher, Abu; Harun-Ur-Rashid, M. (International Journal of Advances in Medicine, 2025)
Background: Hysterectomy, a common gynecological procedure, often involves significant blood loss, making the choice of anesthesia crucial. This study examines the impact of regional versus general anesthesia on intraoperative blood loss and associated complications. To assess the efficacy of regional anesthesia in minimizing intraoperative blood loss and improving postoperative outcomes in hysterectomy patients. Methods: A prospective cross-sectional study was conducted at the Department of Anaesthesia, Analgesia, and Intensive Care Medicine, Bangabandhu Sheikh Mujib Medical University, Dhaka, Bangladesh, from July 2022 to June 2023. A total of 142 patients undergoing elective hysterectomy were included, with 71 receiving regional anesthesia and 71 receiving general anesthesia. Data on intraoperative blood loss, transfusion rates, and postoperative complications were analyzed. Results: Patients in the regional anesthesia group experienced significantly lower mean blood loss (410±65 ml) compared to the general anesthesia group (520±75 ml) (p<0.01). Transfusion was required for 17% of regional anesthesia patients versus 31% of those under general anesthesia (p=0.02). Postoperative nausea and vomiting were less frequent in the regional anesthesia group (7% vs 17%, p=0.03). Conclusion: Regional anesthesia significantly reduces intraoperative blood loss, transfusion needs, and postoperative complications during hysterectomy, promoting better surgical outcomes and patient satisfaction. These findings advocate for the wider adoption of regional anesthesia in elective hysterectomy.